2017
DOI: 10.1186/s12864-017-3896-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide organization and expression profiling of the R2R3-MYB transcription factor family in pineapple (Ananas comosus)

Abstract: BackgroundThe MYB proteins comprise one of the largest families of plant transcription factors, which are involved in various plant physiological and biochemical processes. Pineapple (Ananas comosus) is one of three most important tropical fruits worldwide. The completion of pineapple genome sequencing provides a great opportunity to investigate the organization and evolutionary traits of pineapple MYB genes at the genome-wide level.ResultsIn the present study, a total of 94 pineapple R2R3-MYB genes were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 60 publications
12
78
0
1
Order By: Relevance
“…Members of such groups are important candidates for species-specific functional investigations (Table 2). The phylogenetic results were consistent with recent reports [26,32,47] showing that various groups included more MYBs from Arabidopsis than M. acuminata, M. balbisiana, and O. sativa. These results are in accordance with the current information that Arabidopsis underwent more duplication events after divergence of the last common ancestor from these three close species.…”
Section: Phylogenetic Analysis Of Musa Acuminata and Musa Balbisianasupporting
confidence: 92%
“…Members of such groups are important candidates for species-specific functional investigations (Table 2). The phylogenetic results were consistent with recent reports [26,32,47] showing that various groups included more MYBs from Arabidopsis than M. acuminata, M. balbisiana, and O. sativa. These results are in accordance with the current information that Arabidopsis underwent more duplication events after divergence of the last common ancestor from these three close species.…”
Section: Phylogenetic Analysis Of Musa Acuminata and Musa Balbisianasupporting
confidence: 92%
“…The number of segmental duplications in sea buckthorn was significantly higher than the number of tandem duplications, which had been found in many plants. This suggested that the occurrence of segment duplications might play a more critical role in the expansion of the sea buckthorn R2R3-MYB gene family [29].…”
Section: Chromosome Localization Replication Events and Collinearitymentioning
confidence: 99%
“…The fragments per kilobase of exon per million mapped reads (FPKM) values were calculated based on RNA-Seq reads. The heatmap was generated with TBTOOLS software (https://github.com/CJ-Chen/ TBtools) [31]. The color scale shown represents FPKM counts, and the ratios were log2 transformed.…”
Section: Analysis Of Zjbhlh Gene Expression From Rna-seq Datamentioning
confidence: 99%